Grand Design for Provincial Expansion in Papua from the Perspective of 7 (Seven) Cultural Regions - Esau Hombore; Khasa Efendy; Sampara Lukman; Kusworo (GoAcademica Research & Publishing, 2023)
This research aims to identify seven cultural regions that can contribute to the development of contemporary and future Papua, while adhering to the principles of the Unitary State of the Republic of Indonesia. This study combines the theory of